2017
DOI: 10.1002/ptr.5778
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Jasmonate Ameliorates Testosterone Propionate-induced Prostatic Hyperplasia in Castrated Wistar Rats

Abstract: Benign prostate hyperplasia (BPH) is a progressive disease that is related to age. Known therapeutic agents used in the treatment of BPH are associated with toxicity. Therefore, chemoprevention could be an effective approach. We investigated the ameliorative effects of methyl jasmonate (MeJA) in testosterone propionate (TP)-induced BPH in castrated rats. Castration was performed by removing both testes through the scrotum sack under ketamine anesthesia. Rats were assigned into seven groups of seven animals eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…PSA Content. At the end of the experiment, blood samples were collected under anesthesia directly from the heart for the evaluation of free prostate-specific antigen (PSA) with the PSA ELISA Kit [65].…”
Section: Glutathione (Gsh) Glutathione (Gsh) Measurementmentioning
confidence: 99%
“…PSA Content. At the end of the experiment, blood samples were collected under anesthesia directly from the heart for the evaluation of free prostate-specific antigen (PSA) with the PSA ELISA Kit [65].…”
Section: Glutathione (Gsh) Glutathione (Gsh) Measurementmentioning
confidence: 99%
“…6 rats did not receive TE and just received IM corn oil injection as the normal group (vehicle). Standard medicine group received intramuscular TE and 10 mg/kg body weight finasteride through daily gavage [25]. The design of the experimental procedure used in the study is shown in Table 1.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…After anesthetizing the rats, blood samples were collected from their hearts and sent to an associate laboratory to evaluate free prostate specific antigen (PSA) in the blood using the PSA ELISA kit [25].…”
Section: Psa Contentmentioning
confidence: 99%
“…The use of these two classes of medications is limited because of their adverse effects, including decreased libido, ejaculatory dysfunction and upper respiratory tract infection (Bullock & Andriole, 2006 ). Therefore, alternative medicines for the treatment of BPH are being developed continuously (Akanni et al., 2017 ; Ammar et al., 2015 ; Jena et al., 2016 ; Kim et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%